Medical technology and life expectancy: Evidence from the antitoxin treatment of diphtheria - Philipp Ager; Casper Worm Hansen; Peter Zhixian Lin (European Historical Economics Society (EHES), 2023)
This paper studies the impact of the first effective medical treatment for an infectious disease -diphtheria antitoxin- on the historical health transition in the United States. Using an instrumental variable for local antitoxin adoption rates and information from approximately 1.6 million death certificates from 1880 to 1914, we find that the rapid diffusion of antitoxin led to a substantial decline in diphtheria mortality rates and increased life expectancy at birth. Exposure to antitoxin also significantly reduced school absenteeism. Overall, our results suggest that medicine played a more important role in increasing life expectancy in the early 20th century than previously thought.
Keywords: J11; N32; I15; 330; Life expectancy; medical technology; antitoxin